An analogy of interstitial site occupancy and hydrogen induced disproportionation of Zr1−xTixCo ternary alloys. (23rd March 2017) - Jat, Ram Avtar; Singh, Ripandeep; Pati, Subhasis; Sastry, P.U.; Das, A.; Agarwal, Renu; Parida, S.C.
Abstract: The hydrogen induced disproportionation behavior of Ti-substituted ZrCo alloys was investigated to explore their suitability for International Thermonuclear Experimental Reactor (ITER) Storage and Delivery System (SDS). The isothermal disproportionation studies on Ti-substituted alloys were carried out in conditions simulating ITER SDS i.e. 750 K temperature and 100 kPa hydrogen pressure. It was observed that the rate of disproportionation of Ti-substituted ZrCo alloys was found to vary as ZrCo > Zr0.9 Ti0.1 Co > Zr0.7 Ti0.3 Co > Zr0.8 Ti0.2 Co. X-ray diffraction measurements revealed the formation of TiCoH phase along with Ti-substituted ZrCo2 and ZrH2 phases as a result of disproportionation reaction of alloys. Neutron diffraction measurements on deuterides indicated that deuterium occupancy in 8 e site and the corresponding Zr-D distance provide the primary driving force for disproportionation of alloys to take place. A plausible potential energy profile based on thermodynamic and kinetic considerations was proposed to explain the disproportionation mechanism of alloys. Highlights: Hydrogen induced disproportionation behavior of Zr1−x Tix Co alloys was investigated. Substitution of Zr with Ti improves the durability against disproportionation. Extent of disproportionation is governed by the occupancy of D in 8 e site. Plausible potential energy profile was suggested for disproportionation reaction.